Structure-activity relationship and MM2 energy minimized conformational analysis of quercetin and its derivatives in the DPPH• radical scavenging capacity - Bajracharya, Gan B; Paudel, Mohan; K. C., Rajendra; Shyaula, Sajan L. (BIBECHANA, 2020)
Antioxidant activity of quercetin (1) and its derivatives (2-15) was evaluated by using DPPH assay and IC50 values were calculated. Dihedral angles α of C3-C2-C1’-C6’ chain and β of O1-C2-C-1’-C2’ chain between AC and B rings of these flavones were determined by using MM2 energy minimized structures. Structure-activity relationship study revealed that quercetin (1), quercetin-5-methyl ether (2), quercetin-3’-methyl ether (3) and quercetin-3’,5-dimethyl ether (4) displaying a high antioxidant activity (IC50 = 47.20-119.27 μM) possess similar dihedral angles (α 11.1-11.5º and β 6.3-6.6º). Mono- and/or di-methoxy substituent(s) at 3’ and 5 positions of the flavone are most suitable for the preservation of the antioxidant capacity while retaining conformational geometry. BIBECHANA 17 (2020) 19-26